Innovative Approaches in Business Psychology: A Comprehensive Review and Development Strategies in Jordan - Gharam Abdelaziz; Safwan Al Salaimeh (iRASD Journal of Management)
The business sector in Jordan significantly impacts the economy, which has led to the development of disciplines like commercial psychology, business psychology, and industrial psychology. This paper discusses innovative solutions and developmental trends in these fields. Thus, the research of current methods and techniques allows us to define new models with great potential that can be used in further adaptations. The present paper is a systematic review that seeks to discuss the current practices and present new methods that can improve the efficiency of business psychology. By critically analyzing the literature, this research provides guidelines and suggestions for applying these sophisticated methods in the ideal setting, which is helpful for developing business psychology in different fields.